Wir sind die Anderen : zeitweise. - Demeester, Ann; Hoet, Jan (Herford : MKK gGmbH, 2001)
't Jolle, Sven ; Barry, Orla ; Birza, Rob ; Blome, Astrid ; Cabrita Reis, Pedro ; Chafes, Rui ; Charlier, Jacques ; Copers, Leo ; Diamond, Jessica ; Diesing, Petra ; Dietvorst, Els ; Dimitrijevic, Braco ; Escher, Jürgen ; Fabre, Jan ; Fainaru, Belu-Simion ; Frandsen, Erik A. ; Fusi, Federico ; Garrutti, Alberto ; Gillen, Tina ; Horn, Janis ; Van Imschoot, Jan ; Jochems, Gert ; Kahre, Marlene ; Kokolia, Vladimir ; Lehtonen, Henrietta ; Lopez-Menchero, Emilio ; Maier-Neustadt, Hermann ; Van Mechelen, Koen ; Melgaard, Bjarne ; Mühlenhoff, Hanna Lina ; Najand, Soheila ; Niestrath, Christa ; Ntakiyica, Aimé ; Ontani, Luigi ; Preesman, Avery ; Prum, Antoine ; Rage, Anne-Britt ; Redlin, Emmi ; Sarmento, Julião ; Schatz, Silke ; Smit, Carolein ; Solakov, Nedko ; Stoy, Maria Larissa ; Surúvka, Jiri ; Tuymans, Luc ; Waesch, Wolfgang ; Weinberger, Lois ; Weizenfeld ; Wesemann, Frauke ; Xhafa, Sislej
Duits
Wir sind die Anderen, einer Ausstellung im öffentlichen Raum vom 23. Juni bis 23. Augustus 2001 in Herford
boek